Konsep Perdamaian dalam Tafsir al-Qur’anul Adzīm Karya Ibnu Katsir: Analisis Semanalis hingga Intertekstualitas Julia Keristeva - Muhammad Ebin Rajab Sihombing (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2024)
It turns out that faith alone is not enough for Muslims to carry out their worship, but must be accompanied by a sense of security. A sense of security will arise if humans and their environment are peaceful without conflict and dispute. Therefore, this article will explore how the Qur'an comments on peace. An important aspect in this study is analyzing the concept of peace in Ibnu Katsir's tafsir al-Qur'anul Adzīm, analyzing semi-analytical approaches and Julia Kristeva's intertextuality. This study focuses on QS. an-Nisa 4: 114 uses qualitative methods such as literature review. This research found that reconciliation in the interpretation of the Qur'an al-adzīm is a very noble activity that has received extraordinary appreciation in the Qur'an and as-Sunnah. Based on the theory of Julia Kristeva, QS. an-Nisa and its interpretation cannot be separated from historical construction, so that Ibn Kathir's interpretation in the tafsir al-Qur'anul adzīm undergoes a transposition with the tafsir al-Jami' Ahkam al-Qur'an by Imam al-Qurthubi, which consists of modifications, expansions (add), haplology and parallel.